Measuring the Productivity of Indonesia Waqf Institution (2015-2021): A Malmquist Index - Maulida, Syahdatul; Laila, Nisful (SMART Insight, 2023)
This study aims to measure the productivity of waqf institutions in Indonesia using the Malmquist Productivity Index (MPI) method with the research period 2015-2021. The research objects used are 6 waqf institutions in Indonesia. The data from this study comes from the annual financial statements of each institution from the 2015-2021 period. The input variables in this study are employee costs, operational costs and fixed assets. And for the output variable is the collection and distribution of waqf. The results of this study explain that during the 2015-2021 period, the productivity level of waqf institutions in Indonesia had a fluctuating trend from year to year. Based on the average tfpch score, it is concluded that the productivity of waqf institutions shows an increase and technological change contributes optimally to the increase in the productivity of waqf institutions in Indonesia. Furthermore, the Covid-19 pandemic phenomenon does not have a significant impact on the productivity level of waqf institutions in Indonesia.